2021
DOI: 10.18332/popmed/140132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, knowledge, attitudes and factors associated with exclusive breastfeeding among mothers in Dhaka, Bangladesh: A cross-sectional study

Abstract: INTRODUCTION Exclusive breastfeeding is balanced nutrition for growth and development of the infant, prevents stunting as well as protects from infectious and chronic diseases and has also potential to reduce infant mortality. Thus, the study aimed to assess maternal knowledge, attitudes and other factors associated with exclusive breastfeeding practices. METHODS A cross-sectional study was conducted among 385 mothers of children aged ≤12 months in Mother and Child Hospital in Dhaka city, Bangladesh, from June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
4
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
3
9
4
4
Order By: Relevance
“…Regarding to the women's knowledge about breastfeeding, this study showed the majority of the study sample had a good knowledge regarding breastfeeding. These results were not agree with the results of two studies reported by (Hasan, Hassan, Khan, Tareq, & Afroj, 2021) in Bangladesh, and (Al Ketbi et al, 2018) in Abu-Dhabi the findings were 58.6% and 51.2% respectively.…”
Section: Discussioncontrasting
confidence: 88%
“…Regarding to the women's knowledge about breastfeeding, this study showed the majority of the study sample had a good knowledge regarding breastfeeding. These results were not agree with the results of two studies reported by (Hasan, Hassan, Khan, Tareq, & Afroj, 2021) in Bangladesh, and (Al Ketbi et al, 2018) in Abu-Dhabi the findings were 58.6% and 51.2% respectively.…”
Section: Discussioncontrasting
confidence: 88%
“…In contrast to family income, which had a p-value > 0.05 and was statistically insignificant, mothers who were older (> 25 years), had greater levels of education (> the 10th grade), were housewives, and had more children had a good understanding of and practice in breastfeeding. Except for family wealth, this result was consistent with the study conducted by Bangladeshi researchers Hassan M et al [10]. However, Hassan M. et al found that family income had a statistically significant p-value (<0.05), which is different from the results of the current study (p-value=>0.05) [10]…”
Section: Discussionsupporting
confidence: 84%
“…A total of 400 mothers were included in the study, with 78% of them under the age of 25 and the remaining 22% above. Compared to the current study, Hasan M et al found that 54.5% of mothers were under the age of 24 [10] since the current study included 77% of primi mothers whereas their study only included 52.9%. In accordance with the location of this medical college, 93% of mothers were from rural areas, while only 7% were from metropolitan areas.…”
Section: Discussioncontrasting
confidence: 69%
“…Factors affecting good practices differed from others studies in literature. In Hasan et al (2021), mode of delivery, number of children, and education level were among factors that affected practice of mothers.…”
Section: Discussionmentioning
confidence: 99%